1996
DOI: 10.1128/iai.64.1.189-196.1996
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interleukin 12 neutralization on host resistance and gamma interferon production in mouse typhoid

Abstract: Innately resistant (Ity r) A/J mice infected with the virulent Salmonella typhimurium C5 strain suppress the early exponential bacterial growth in the reticuloendothelial system toward the end of the first week of infection, with spleen and liver bacterial counts reaching a plateau phase. In vivo administration of neutralizing anti-interleukin-12 (IL-12) antibodies did not affect early bacterial growth in the tissues (days 1 to 3) but impaired the establishment of the plateau, with higher spleen and liver coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(47 citation statements)
references
References 26 publications
1
46
0
Order By: Relevance
“…As these mice resist secondary infection, this model also allows for antibody-mediated depletion of cell populations or cytokines to assess the role of these in Salmonella immunity. These experiments have confirmed the importance of both CD4 + and CD8 + T cells during protective immunity and demonstrated that IL-12, IFN-c, TNF-a, and iNOS each play important roles in mediating bacterial killing (8,9,85,86). It is surprising therefore that the adoptive transfer of spleen cells from immune to na€ ıve mice is insufficient to transfer protective immunity (11).…”
Section: T-cell Response To Salmonella Infectionmentioning
confidence: 90%
“…As these mice resist secondary infection, this model also allows for antibody-mediated depletion of cell populations or cytokines to assess the role of these in Salmonella immunity. These experiments have confirmed the importance of both CD4 + and CD8 + T cells during protective immunity and demonstrated that IL-12, IFN-c, TNF-a, and iNOS each play important roles in mediating bacterial killing (8,9,85,86). It is surprising therefore that the adoptive transfer of spleen cells from immune to na€ ıve mice is insufficient to transfer protective immunity (11).…”
Section: T-cell Response To Salmonella Infectionmentioning
confidence: 90%
“…As is clear from the data of human patients IL-12 is important to control Salmonella infections. 112 This may relate to IFN-g function, as IL-12 is a potent activator of IFN-g production. However, it may also be in part due to IFN-g independent IL-23mediated effects as discussed above.…”
Section: Murine Cytokines In Control Of Salmonella Infectionmentioning
confidence: 99%
“…Role of the IL-12 family members in infectious diseases IL-12 has a key role in protection against intracellular protozoan, fungal and bacterial infections [4,5,40,52,53] ( Table 2). The role of IL-12 in protection and pathology during viral infections depends on the type of virus [54 -57].…”
Section: Il-27 (Ebi3-p28) -The Early Riser In Th1 Responses Which Wamentioning
confidence: 99%